Advances in Manufacturing Technologies and Production Engineering - Afolabi Daniyan, Ilesanmi (Bentham Science Publishers, 2022)
This reference presents a collection of studies which highlight new developments in improving manufacturing processes and performance. The book includes 11 chapters which cover unique topics of interest to production engineers. These topics include the production of advanced composite materials and alloys to the use of sensors to evaluate production processes, product testing and evaluation (in production and storage environments), and the development and testing of an unmanned aerial vehicle.Chapters have been contributed by several scholars, who give a unique perspective on specific aspects of manufacturing and industrial production. The book also covers recent technologies such as additive manufacturing. Each chapter presents the study in an experimental manner highlighting the theory, methods, and results, where applicable. References for further reading are also provided.This book is intended to provide researchers and engineers with new data and cases for industrial manufacturing processes which may be applied in different industrial sectors.